E-Book on Ethno-conservation of Agricultural Land for Teaching Students' Critical Thinking Skills in Sidoarjo-Indonesia - Moch. Yogi Pratama; Sunu Kuntjoro; Mahanani Tri Asri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to test the effectiveness of an e-book on the ethno-conservation of agricultural land in Sidoarjo for teaching students critical thinking skills in environmental conservation material. Critical thinking ability is one of the higher-order thinking skills in Bloom's taxonomy and needs to be applied in the learning process. Critical thinking skills need to be trained in students to solve problems in their environment. Method: The method used in this study is a one-group pre-test and post-test design with 15 students from the science program. The e-book had already undergone feasibility and practicality tests before being implemented in the learning process. The effectiveness test consisted of 5 multiple-choice questions and six essay questions tested for feasibility. Data processing was done using Ms. Excel and SPSS. Results: The Wilcoxon test results showed that using the e-book oriented towards the local wisdom values of Sidoarjo in environmental conservation material affects teaching students critical thinking skills. Novelty: The results of this research can be used as a reference for learning media integrated with local wisdom values to teach students critical thinking skills.